Design of rotational particle structure with negative Poisson's ratio using numerical method - Lee, M. K.; Choi, J. B.; Choi, K.; Lim, H. N. (ECO-MATERIALS PROCESSING AND DESIGN VIII, 2007)
In the area of biomaterials, the structures with negative Poisson's ratio are able to be applied to the polymer component of prosthesis, artificial blood-vessel and catheter. To induce its characteristic, previous studies postulated many structural shapes such as non-convex shape with re-entrant corners and re-entrant honeycomb. In this study, we proposed the rotational particle structures and investigated the Poisson's ratio and the ratio (E-e/E) of the elastic modulus of these structures based on structural design variables using finite element method. The auto-meshing preprocessor was coded using MATLAB in order to construct numerical models as design variables and perform finite element analysis (FEA) effectively. Three selected design variables were the ratio of fibril's length to particle's diameter (0.2-2.0), the ratio of fibril's length to its width (0.02 similar to 0.2) and the angle of fibril about horizontal axis (0 degree similar to tangential angle). Finite element model has 2D plain stress quadratic element and composed of 515 particles and 6-linked fibrils per each particle. For all of 213 cases, one side of each model is applied a tension, 0.1% strain and analyze Poisson's ratio and the ratio (E-e/E) of the elastic modulus. As the ratio of fibril's length to particle's diameter increased and the ratio of fibril's diameter to fibril's length decreased fixing the fibril's angle with 45 degree, the negative Poisson effect of rotational particle structures increased. The ratio of elastic modulus of these structures decreased with Poisson's ratio. The results show the reasonable values as compared with the previous analytical results.